If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 10 + -3u Solving 7 = 10 + -3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '3u' to each side of the equation. 7 + 3u = 10 + -3u + 3u Combine like terms: -3u + 3u = 0 7 + 3u = 10 + 0 7 + 3u = 10 Add '-7' to each side of the equation. 7 + -7 + 3u = 10 + -7 Combine like terms: 7 + -7 = 0 0 + 3u = 10 + -7 3u = 10 + -7 Combine like terms: 10 + -7 = 3 3u = 3 Divide each side by '3'. u = 1 Simplifying u = 1
| 5a-2=3a+4 | | 2(x-4)+12=x-4(6+2x)+9x | | 12×-1/3 | | 13=10 | | 3log(2)x=28 | | -53/4-31/2= | | 4x-40=13-6x+3 | | 2y-10x=10 | | 3.50x=10.50 | | 3x^2+10=100 | | 2x+7=15+4x | | 2x+12+9=x+3 | | 6x+5+9x-10+80+90=360 | | X+6=-8x+5 | | (x^2+0.8)(x^2+0.8)= | | 3x-29=17-5x | | 18=9+3h | | 7tanx+2=9 | | 3y+6-2=8-2y | | 7/3*8/6 | | -4/7y16 | | 12=15-3p | | 2(x-4)+12=x-4(6+2x)+9 | | 42r^2-35r=0 | | -5+1y=-8x | | 15=2v+3 | | 9p-4q=-15 | | 8=10-2r | | -6x+3=-6x-5 | | 4x+7x-8=-19 | | 40=5e | | 3x^2+7=301 |